Evaluation of Civil Engineering Students Readiness and Competency for Building Information Modeling (BIM) Implementation in The Workplace - Aura Nita Mufidah; Redityo Januardi; Dani Nugroho Saputro (Jurnal Ilmiah Dinamika Rekayasa, 2026)
The increasing adoption of Building Information Modeling (BIM) in the construction industry has driven the integration of BIM into higher education curricula. However, evaluations of students’ readiness and competence to implement BIM in the workplace remain limited. This study aims to evaluate the factors that influence students’ readiness and competence in implementing BIM in the workplace. The study employed a quantitative approach targeting undergraduate students in the Civil Engineering program at Jenderal Soedirman University who had completed the “Building Structural Drawing” course. Readiness was analyzed using SEM-PLS, while competency was evaluated through an unofficial Autodesk Certified User (ACU) Revit simulation. The results indicate that the learning ecosystem and academic self-confidence significantly influence students’ readiness, whereas BIM facilities and the comprehensiveness of course materials and assignments provided by instructors do not have a significant effect. The non-significance of facilities suggests that basic access to learning resources is not the main differentiating factor for readiness, while the gap between perceived readiness and ACU performance indicates that confidence developed through familiar modeling tasks may not transfer fully to the less-practiced conceptual and advanced features assessed by ACU. Most students do not yet meet the ACU Revit entry-level competency standards, particularly in the areas of elements and families, as well as stair and site modeling. Therefore, BIM instruction should be directed toward strengthening practical competencies through evaluations based on industry standards.